Estimation of the future behaviour of the sea level in the Canary Islands from the analysis of recent records - Fraile Jurado, Pablo; Sánchez Rodríguez, Esperanza; Fernández Díaz, Miguel; Pita López, María Fernanda; López Torres, José Manuel (Geographicalia, 2015)
The aim of this paper is to estimate the future mean sea level rise in the Canary Islands by means of the analysis of tide gauge and altimetry satellite records. The applied methodology consists of a linear regressionan alysis between global and local time series sea level rise data over the same time period. An equation of the linear regression line is obtained for each pair of data in the time series (global and local), corresponding values for three IPCC scenarios in the global variable are identified, and a local prediction is obtained. A higher sea level rise than IPCC predictions have been found in two of the analyzed tide gauges and in most of the studied water surface. Obtained results in Lanzarote show lower sea level rises than IPCC predictions by the end of the 21st century.